2017
DOI: 10.1128/jb.00058-17
|View full text |Cite
|
Sign up to set email alerts
|

MS2 Lysis of Escherichia coli Depends on Host Chaperone DnaJ

Abstract: The L protein of the single-stranded RNA phage MS2 causes lysis of Escherichia coli without inducing bacteriolytic activity or inhibiting net peptidoglycan (PG) synthesis. To find host genes required for L-mediated lysis, spontaneous Ill (insensitivity to L lysis) mutants were selected as survivors of L expression and shown to have a missense change of the highly conserved proline (P330Q) in the C-terminal domain of DnaJ. In the dnaJ P330Q mutant host, L-mediated lysis is completely blocked at 30°C without aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Two genetics-based approaches were mounted, the first aimed at identifying host factors, using, as before, inducible plasmid-based clones of L (81,82). To avoid mutations that reduced the copy number or L transcription, a blue/white reporter plasmid was constructed, and from hundreds of colonies surviving L induction from this construct, two blue colonies were identified and designated as ill (insensitive to L lysis) mutants (82). Surprisingly, the ill mutations mapped to dnaJ, which encodes a widely conserved chaperone involved in the heat shock response (83).…”
Section: Back To L: Genetic and Molecular Analysismentioning
confidence: 99%
“…Two genetics-based approaches were mounted, the first aimed at identifying host factors, using, as before, inducible plasmid-based clones of L (81,82). To avoid mutations that reduced the copy number or L transcription, a blue/white reporter plasmid was constructed, and from hundreds of colonies surviving L induction from this construct, two blue colonies were identified and designated as ill (insensitive to L lysis) mutants (82). Surprisingly, the ill mutations mapped to dnaJ, which encodes a widely conserved chaperone involved in the heat shock response (83).…”
Section: Back To L: Genetic and Molecular Analysismentioning
confidence: 99%
“…Nonetheless, the molecular information and functioning schema of such an autolytic pathway have yet to be identified [ 82 ]. Recent findings have indicated that the lysis of host cells by MS2 lysin is dependent on a range of host factors, including host chaperone DnaJ [ 106 ]. This post-translational regulator allows for another level of control of both quantity and activity of the lysis protein of MS2.…”
Section: Leviviridaementioning
confidence: 99%
“…Dual functions for PPH in peptidoglycan hydrolysis and blocking cell division are consistent with descriptions of single lysis proteins in phages with smaller genomes. For example, coliphages X174, MS2, and Q␤ encode lysis proteins E, L, and A 2 , respectively (65)(66)(67)(68). Protein E causes host cell lysis by inhibiting the activity of a host protein involved in peptidoglycan biosynthesis (66).…”
Section: Phage Endolysin Triggers Lysis Of a Tumefaciensmentioning
confidence: 99%